FUNGSI KOMUNIKASI MASSA DALAM TELEVISI (Studi Kasus Program Acara Bukan Empat Mata di TRANS 7) - Nora, Hastika Yanti; Latief, Muhammad Chaerul; Setiawan, Yuliyanto Budi (Jurnal The Messenger, 2010)
This research is conducted to described and verified communication functions on television program called Bukan Empat Mata on Trans7. This research used survey method. Primary data gathered from questionnaires, while secondary data collected from related literatures. Research final gains, showing that Bukan Empat Mata serves two mass-communication functions, which are surveillance and linkage functions from media upon society, especially Bukan Empat Mata audiences come from Semarang University academics.